Neurological diseases in Peru: a systematic analysis of the global burden disease study - Carlos ALVA-DÍAZ; Andrely HUERTA-ROSARIO; Kevin PACHECO-BARRIOS; Roberto A. MOLINA; Alba NAVARRO-FLORES; Wilfor AGUIRRE-QUISPE; Nilton CUSTODIO; Juan TORO-PEREZ; Nicanor MORI; Roberto ROMERO-SANCHEZ (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Disease burden indicators assess the impact of disease on a population. They integrate mortality and disability in a single indicator. This allows setting priorities for health services and focusing resources. Objective: To analyze the burden of neurological diseases in Peru from 1990-2015. Methods: A descriptive study that used the epidemiological data published by the Institute for Health Metrics and Evaluation of Global Burden of Diseases from 1990 to 2015. Disease burden was measured using disability-adjusted life years (DALY) and their corresponding 95% uncertainty intervals (UIs), which results from the addition of the years of life lost (YLL) and years lived with disability (YLD). Results: The burden of neurological diseases in Peru were 9.06 and 10.65%, in 1990 and 2015, respectively. In 2015, the main causes were migraine, cerebrovascular disease (CVD), neonatal encephalopathy (NE), and Alzheimer’s disease and other dementias (ADD). This last group and nervous system cancer (NSC) increased 157 and 183% of DALY compared to 1990, respectively. Young population (25 to 44 years old) and older (>85 years old) were the age groups with the highest DALY. The neurological diseases produced 11.06 and 10.02% of the national YLL (CVD as the leading cause) and YLD (migraine as the main cause), respectively. Conclusion: The burden of disease (BD) increased by 1.6% from 1990 to 2015. The main causes were migraine, CVD, and NE. ADD and NSC doubled the DALY in this period. These diseases represent a significant cause of disability attributable to the increase in the life expectancy of our population among other factors. Priority actions should be taken to prevent and treat these causes.